Information and Communication Technology Use, Social Support, and Life Satisfaction among Korean Immigrant Elders. Issue 47 (4th July 2021) - Jun, Jung Sim; Galambos, Colleen; Lee, Kyoung Hag
Abstract: This study recruited 150 community dwelling Korean immigrant elders to understand the role of information and communication technology (ICT) use on social support and life satisfaction by utilizing purposive sampling methods. Hierarchical multiple regression results indicated that a high level of smartphone use was significantly related to a high level of social support from families. High levels of smartphone use and social media use were significantly related to a high level of social support from friends. In addition, a high level of social media use was significantly related to a high level of life satisfaction among Korean immigrant elders. The findings of this study may provide insights for social service practitioners working with Korean immigrant elders to develop culturally appropriate services by using ICTs for improving social support systems and quality of life among the population. Future research with a longitudinal and experimental design can be conducted to better understand the long-term patterns of findings and causal relationships.